Conceptual Issues of Sustainable Development of the Region - Chagelishvili-Agladze, Lali; Gonashvili, Maya; Dalakishvili-Chichinadze, Rusudan ("Intercultural Dialogues" Transactions, 2023)
Sustainable development of regions, full and effective use of their economic potential is very important for the sustainable development of the country's economy. Georgia has a very rich regional potential, the purposeful and rational use of which ensures the ecological security of the region and promotion of sustainable development. As a result of this, the ecological and social effectiveness of the region will be achieved. Environmental problems belong to the category of global problems, their correct solution will contribute to the successful implementation of such issues as: reproduction of renewable resources, effective replacement of alternative resources, use of secondary waste, reduction of environmental pollution and others. The paper analyzes the regional potential of Georgia and presents the main directions of sustainable development.